Investigations on Growth, Optical and Thermal Properties of Sulphamic Acid Single Crystals - D. Jaishree; G. Kanchana; R. Kesavasamy (Advances in Condensed Matter Physics)
Single crystals of sulphamic acid of 11 × 7 × 3 mm3 dimension were successfully grown by slow evaporation technique. The crystal structure of grown crystals was confirmed by single crystal X-ray diffraction analysis. The presence of functional groups in the crystal lattice has been qualitatively determined by FT-IR and FT-Raman analyses. Theoretical group factor analysis predicts the possible modes of vibrations. The optical transmission spectroscopy (UV-Vis) clearly evidences the suitability of this material for optical application. The thermal behaviour of the crystal was studied by thermogravimetric (TG) and differential scanning calorimetric (DSC) studies. The nonlinear optical (NLO) characteristic of this material was explored by the second harmonic generation (SHG) conversion efficiency.